(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Trividha Pareeksha’s like Darshana, Sparshana and Prashna holds relevance in the current clinical methods like history taking, general examination and systemic examinations. ‘Rogamadou Pareekshet Tathoanantharam Oushadam’ before planning any treatment one should have completes knowledge of Roga and Rogibala. From ancient time to till date examination of patient is important. Vyadhiutpathi always lead to disrupted body system and after that body is need to be investigated by various protocols, Pariksha are one among them. Rogi pariksha is an important parameter in the diagnosis of a disease as before diagnosis the treatment of a disease is not possible. Examining the patient is a skillful act and well as in contemporary science both have explained this examination elaborately. Prakrut avastha Rogi Pariksha are dealt in Ayurveda. Principle of Ayurveda is to take care of individual health and to relieve the ailing individual for disease. Acharyas have given a variety of examination in the form of Pariksha. Pariksha are the diagnostic tool that helps to diagnose the Vyadhi. Hence in this present study individual different Prakrutis were selected for the study and each Prakruti assessment is done and Darshana Pareeksha is defined, comparing to the variables of blood components and urine. Here in this present study Darshana Pareeksha is considered as a major role in different Prakruti is observed with respect to blood and urine. Darshana variables are compared to CBC variables and urine variables. A complete blood count (CBC) gives important information about the kinds and numbers of cells in the blood, especially red blood cells, white blood cells, and platelets.